Establishing a West African chrono-cultural framework: First luminescence dating of sedimentary formations from the Falémé Valley, Eastern Senegal - (:unkn) unknown (My University, 2016)
Recent studies have shown that the Falémé Valley, located in eastern Senegal, is a major component in the comprehension of the West African Palaeolithic period. Several of the sites discovered in this region show a wide variety of lithic productions attributed to the Early, Middle and Later Stone Age.Optically stimulated luminescence dating of 16 samples coming from five sites produces evidence of archaeological records from at least Marine Isotope Stage 5, highlighting an ancient human presence. The dates also indicate nearly continuous sedimentary deposits over the entire upper Pleistocene. In particular, at least one archaeological level is positioned within Marine Isotope Stage 2, which is poorly documented in West Africa. Thus interestingly, the Falémé sequence completes the sequence of Ounjougou in Mali, which was considered up to now as the unique key element for the definition of the chrono-cultural framework of this region.
Keywords: African Research